Mental Representations of Time in English Monolinguals, Mandarin Monolinguals, and Mandarin–English Bilinguals - Yang, Wenxing; Gu, Yiting; Fang, Ying; Sun, Ying (Frontiers in Psychology, 2022)
This study recruited English monolinguals, Mandarin monolinguals and Mandarin-English (ME) bilinguals to examine whether native English and native Mandarin speakers think about time differently and whether the acquisition of L2 English could reshape native Mandarin speakers’ mental representations of temporal sequence. Across two experiments, we used the temporal congruency categorization paradigm which involved two-alternative forced-choice reaction time tasks to contrast experimental conditions that were assumed to be either compatible or incompatible with the internal spatiotemporal associations. Results add to previous studies by confirming that native English and native Mandarin speakers do think about time differently, and the significant cross-linguistic discrepancy primarily lies in the vertical representations of time flow. However, current findings also clarify the existing literature, demonstrating that the acquisition of L2 English does not appear to affect native Mandarin speakers’ temporal cognition. ME bilinguals, irrespective of whether they attained elementary or advanced level of English proficiency, exhibited temporal thinking patterns commensurate with those of Mandarin monolinguals. Some theoretical implications regarding the effect of bilingualism on cognition in general can be drawn from the present study, a crucial one being that it provides evidence against the view that L2 acquisition can reshape habitual modes of thinking established by L1.